An investigation into linguistic features of english and vietnamese proverbs denoting Love and marriage - Lại Thị Ngọc Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study investigates linguistic features of English and Vietnamese proverbs denoting love and marriage. It focuses on analyzing and comparing the syntactic features, semantic features and stylistic devices English proverbs and Vietnamese ones. Basing on the description and analysis on distinguishing features, the similarities and differences of proverbs in the two languages are presented. The data includes 300 samples in English and Vietnamese, from various linguistic books, dictionaries and from the internet and they are analyzed both qualitatively and quantitatively. The findings reveal that both EPLM and VPLM share three types of phrasal structures, four types of sentential structures and they indicate three kinds of meanings: literal meaning, figurative meaning and literal-figurative meaning. The results also show that both EPLM and VPLM are used as stylistic devices such as rhyme, metaphor, simile, etc. These findings lead to some implications for the language learning and teaching. It is hoped that the study will be useful to those who teach and study English as well as ones who are interested in proverbs denoting love and marriage